Bilateral vertebral artery dissection, agenesis of both ICAs, and connective tissue aberrations - Lill, Christina Maria; Günther-Kunkel, Kristin; Hoch, Heinrich; Paul, Friedemann; Grond-Ginsbach, Caspar; Haußer-Siller, Ingrid; Zipp, Frauke (Neurology, 2013)
A 35-year-old woman presented with acute signs of stroke (appendix e-1 on the Neurology® Web site at [www.neurology.org][1]). After initial CT with angiography, MRI with time-of-flight angiography confirmed agenesis of both internal carotid arteries (ICAs; figure 1A). It revealed bilateral vertebral artery (VA) dissections and ischemias in both middle artery territories (figure 1, A-E). Skin biopsy microscopy (figure 2) was consistent with ultrastructural connective tissue disease (uCTD), for which no further evidence was found apart from mild hypermobility of the finger joints. The underlying uCTD with structural instability of the arterial walls and the increased blood flow in the vertebrobasilar circulation due to the bilateral ICA agenesis may have promoted VA dissection. - - [1]: http://www.neurology.org/